PENINGKATAN MASSA OTOT MELALUI RESISTANCE TRAINING: STUDI EKSPERIMEN ENAM MINGGU PADA ATLET KARATE JUNIOR - Farrel, Indra William; Rismayadi, Alen; Mulyana, Mulyana; Kusumah, Widi; Novian, Geraldi (YLPK Mahardhika, 2025)
Strength development in junior karate athletes is an important aspect because it plays a direct role in supporting performance, both during training and in competitions. However, the applied training pattern is often lacking in variety and is not optimally structured. This study aims to examine the effect of a six-week resistance training program on increasing muscle mass in junior karate athletes. The method used was an experiment with a one-group pretest-posttest design, involving 15 athletes consisting of 8 boys and 7 girls aged 13–15 years. The treatment in the form of resistance training was carried out twice a week, with a training program that included two upper body movements (bench press and upper back row) and two lower body movements (squat and leg extension). The load used was more than 15 RM with a movement tempo of 2–8 seconds. Muscle mass measurements were taken before and after the intervention using the Karada Scan Omron HBF-701, then analyzed through a t-test with the help of SPSS Version 29. The results showed a significant increase in muscle mass of 9% after undergoing resistance training. These findings indicate that a systematically designed resistance training program can help junior karate athletes in increasing strength and speed. Thus, coaches are advised to integrate resistance training into their coaching programs to support the achievement of optimal performance.